Combined trabeculotomy-trabeculectomy with antimetabolite and releasable suture: outcome with primary congenital glaucoma in a north Indian population - Dubey, S; Agrawal, A; Chauhan, L; Mukherjee, S; Douglas, G (Nepalese Journal of Ophthalmology, 2015)
Objective: To determine the surgical outcomes of combined trabeculotomy- trabeculectomy with mitomycin-C and releasable suture in children with primary congenital glaucoma (PCG) in a North Indian population. Design: Retrospective, interventional, consecutive, non-comparative case series. Materials and methods: The medical records of 137 eyes of 77 patients who underwent combined trabeculotomy- trabeculectomy with 0.2 mg/ml mitomycin C (MMC) either bilaterally (49 patients) or unilaterally (28 patients) between January 2004 and March 2012 were reviewed retrospectively. The main outcome measures were postoperative intraocular pressures, corneal clarity and diameter, duration of follow-up, success rate and complications. Results: The mean preoperative intraocular pressure reduced from 34 ± 7 mm Hg (range 15- 54 mm Hg) to 17 ± 7 mm Hg (range 5 - 32 mm Hg) with a mean reduction of 44 % (P < 0.001). The mean follow-up period was 24.4 ± 10.3 months (range 6 – 48 months). Complete success defined as intraocular pressure < 21 mm Hg without any medication and clinically stable glaucoma at last follow-up was achieved in 113 eyes (83 %) while a ‘quali¿ed success’ of intraocular pressure < 21 mm Hg with one medication was achieved in ten eyes (7 %). The Kaplan-Meier survival analysis revealed success rates (at ‘n’ months) of 90 % (6), 85 % (12), 82 % (24), 80 % (36) and 77 % (48). There were no signi¿cant intraoperative or postoperative complications.Conclusion: Primary combined trabeculotomy-trabeculectomy with mitomycin-C and releasable suture offers a viable surgical option in Northern Indian infants with primary congenital glaucoma. The use of 0.2 mg/ml mitomycin C for 2 minutes improves the overall success while the releasable suture decreases the risk of postoperative complications especially associated with the use of antimetabolites.